Gasification Characteristics of High Moisture Content Lignite under CO2 and Auto-Generated Steam Atmosphere in a Moving Bed Tubular Reactor - Haojie Gao; Zhisong Wen; Lizhu Jin; Xin Xiong; Yuezhao Zhu (Energies, 2022)
An external thermal high-temperature continuous feed moving bed tubular reactor was used for the gasification of high moisture content lignite (30.41 wt.%) under CO2 and an auto-generated steam atmosphere. The objectives of this study are to illustrate the synergistic gasification characteristics of high moisture content lignite and CO2 in the tubular reactor; CO2 and auto-generated steam (steam released from the lignite) were used as gasification agents for lignite gasification. The effects of temperature and CO2 flow rate were also investigated. Experimental results showed that when the gasification temperature increased from 800 °C to 1000 °C, the H2 yield also increased from 8.45 mol kg−1 to 17.86 mol kg−1. This may indicate that the H2O-CO2 gasification of semi-coke was enhanced with the rise in temperature. At 900 °C, the gas yield increased with the increase in CO2 flow rate, while the yield of char and liquid product showed an opposite trend. The lower heating value of the H2-rich syngas varied from 11.73 MJ m−3 to 12.77 MJ Nm−3. The experimental results proved that the high moisture content lignite in-situ CO2 gasification process is an effective methodology for the clean and efficient utilization of lignite.